Factors that influence the final grades of students in managerial accounting course in De La Salle University - Cudia, Cynthia P. (Animo Repository, 2009)
Many research studies about appropriate pedagogic practices resulted from the worldwide concern about the teaching strategies that affect student-learning outcomes. This study attempts to contribute to the demands of continuous improvement in pedagogic practices of school by investigating the factors that predict the performance of students. In particular, the researcher employed statistical data of selected students of one of the business schools in the Philippines, De La Salle University, Manila (DLSU). The university offers managerial accounting for business students, which combines the knowledge of management practice and the use of accounting information. Based on 478 observations, result from the statistical tests done revealed that the variables—number of quizzes, gender, and course affiliation—have an impact on the performance of students, as reflected in their final grades. Findings from this study have implications for educators and grade policy-makers who are interested in the assessment of student performance. These implications can aid in developing remedial tools that lead to educational improvement.